2023
DOI: 10.1021/acsomega.2c07481
|View full text |Cite
|
Sign up to set email alerts
|

Butylene Glycol Used as a Sustainable Solvent for Extracting Bioactive Compounds fromCamellia sinensisFlowers with Ultrasound-Assisted Extraction

Abstract: The research aims to assess the yield of bioactive compounds and their antioxidant activities obtained from tea flowers using an ultrasound-assisted extraction method with butylene glycol (BG-UAE) through Box−Behnken design. It investigates the bioactive compounds including the total phenolic content (TPC), total flavonoid content (TFC), and total tannin content (TTC) and analyzes their antioxidant activities, bioactive compound composition by liquid chromatography triple quadrupole tandem mass spectrometry, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…1 ). Previous studies supported the findings that alcohol-water mixtures enhanced the extraction yield of bioactive compounds [ 14 , 15 , 24 ].
Fig.
…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…1 ). Previous studies supported the findings that alcohol-water mixtures enhanced the extraction yield of bioactive compounds [ 14 , 15 , 24 ].
Fig.
…”
Section: Resultssupporting
confidence: 63%
“…Earlier research on the UAE of coffee pulp with an aqueous-propylene glycol mixture and tea flower with an aqueous-BG mixture showed that TPC, as well as antioxidant activities, remained relatively unchanged with prolonged extraction duration. However, these values exhibited an increase with higher solvent-to-sample ratios until reaching a saturation point, beyond which additional solvent did not lead to further enhancement in response values [ 14 , 15 ]. In contrast, Pandey et al (2018) found that the duration of extraction did not significantly affect response values such as TPC, ABTS, and DPPH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations